ENGLISH WRITING ANXIETY TOWARD INDONESIAN EFL LEARNERS: A DESCRIPTIVE STUDY - Mohammad Rudiyanto (INTERAKSI : Jurnal Kependidikan, 2017)
This study aims at investigating English writing anxiety toward Indoensian EFL learners. There were 39 students comprised of 16 male students and 23 female students who participate in this study of Indonesian State Senior High School. This current study used descriptive design with explanatory sequential mixed method approach. In quantitative phase, there were three questionnaires that are employed to collect data, namely SLWAI, CWAI, PLPSQ, as well as English writing test to collect students’ English writing score. In qualitative phase, this study collected the qualitative data through interviews. The analysis results revealed that the student experience medium level of somatic anxiety in which the female students were identified significantly more anxious than the male students. The major factors that caused the student experience English writing anxiety were insufficient writing practice, linguistic difficulties, insufficient writing technique and writing in time constraint. It was also found that English writing anxiety had positive effect toward the students’ writing performance. There were pedagogical implications addressed to English teacher and recommendations for future research that are suggested by this study.